A study on evaluation method of crack tip reverse plastic zone size for the center cracked steel plate model under tension–compression cyclic loading. (January 2015) - Chen, Jingjie; Huang, Yi; Dong, Leilei; Li, Yugang
Highlights: We propose an evaluation method for crack-tip reverse plastic zone size (CTRPZS). The effect of compressive loads on CTRPZS is considered. The expression of CTRPZS under compressive loading stage is acquired. The expression is suitable for center cracked finite plates with different material. Abstract: An evaluation method of the crack tip reverse plastic zone size (CTRPZS) for the center cracked steel plate under tension–compression cyclic loading is proposed. In this method, the variable quantity of maximum crack opening displacement (VMCOD) is used to study the effect of compressive loads on CTRPZS. In the compressive loading stage, CTRPSZ increases linearly with increasing of the compressive load on basis of the existing CTRPZS after the tensile loading and tensile unloading processes. The maximum CTRPZS can be expressed with respect to VMCOD. This expression is suitable for center cracked finite plates with different materials under tension–compression cyclic loading.